Manager’s effort and endogenous economic discrimination - Orrillo, Jaime; Loureiro, Paulo R. A. (Estudos Econômicos (São Paulo), 2004)
Assume a labor supply consisting of two types of workers, 1 and 2. Both workers are equally productive and exhibit supply functions with the same elasticity. We consider a firm (entrepreneur or shareholders) that is competitive in the output market and monopsonistic in input markets. The firm uses the services of a manager who has a high human capital and whose wage is given by the market. It is supposed that the manager does not like to work with one type of worker, say type 1. If we allow the manager's effort to be an additional input without any extra (in addition to his salary) cost for the firm, then the firm's pricing decision will be different for both workers. That is, there will be a wage differential and therefore endogenous economic discrimination2 in the labor markets.